{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

NFALtoNFA - NFA to NFA conversion Purpose • This...

Info iconThis preview shows pages 1–6. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: NFA- λ to NFA conversion Purpose • This presentation presents an example execution of the algorithm which takes as input an NFA with λ-transitions and produces as output an equivalent NFA without λ- transitions • Algorithm Specification – Input: NFA M 1 with λ-transitions – Output: NFA M 2 without λ-transitions Input NFA M 1 with λ- transitions λ λ λ a a b b a,b 1 2 3 4 5 Compute all Λ- closures λ λ λ a a b b a,b 1 2 3 4 5 While this step is not necessary, it does make all future steps simpler. Compute Λ ({i}) for 0 < i < 6 Λ ({1}) = {1,2,3} Λ ({2}) = {2} Λ ({3}) = {3} Λ ({4}) = {4} Λ ({5}) = {5,1,2,3} = {1,2,3,5} Process State 1 λ λ λ a a b b a,b 1 2 3 4 5 Compute δ * (1,b) First compute Λ ({1}) Λ ({1}) = {1,2,3} Now compute δ(Λ ({1}) ,b) δ (1,b) = {} δ (2,b) = {4} δ (3,b) = {3} δ(Λ ({1}) ,b) = {3,4} Finally compute Λ ( δ(Λ ({1}) ,a)) = Λ ({3,4}) Λ ({3}) = {3} Λ ({4}) = {4} Λ ( δ(Λ ({1}) ,b)) = {3,4} δ * (1,b) = {3,4} Compute δ * (1,a)...
View Full Document

{[ snackBarMessage ]}

Page1 / 11

NFALtoNFA - NFA to NFA conversion Purpose • This...

This preview shows document pages 1 - 6. Sign up to view the full document.

View Full Document Right Arrow Icon bookmark
Ask a homework question - tutors are online